Re-Storying the Colonial Landscape: Richard Wagamese’s Indian Horse - Robinson, Jack (Studies in Canadian Literature, 2013)
The narratives of Anishinaubae author Richard Wagamese, whether autobiographical or fictional, are representations of his own journey, vehicles of personal and cultural reconstruction. Indian Horse is another such narrative. It is possible to read the novel as being exclusively about residential schools or hockey or both. These topics require attention in order to understand the depiction of Saul Indian Horse’s wounded spirit and of what Eduardo and Bonnie Duran call the "soul wound" of his people. Yet close textual analysis shows how the text uses oral storytelling techniques to render Saul’s journey of personal re-creation: his reclamation of a healthy form of Indigenous masculinity, of his visionary power, of a spiritual connection with the land, of relationships with his extended kinship family, and of a sense of gender complementarity and reverence for the feminine.